Paya Kepala Sekolah Dalam Meningkatkan Kemampuan Guru Dalam Memanfaatkan Lingkungan Sebagai Sumber Belajar Dengan Menggunakan Diskusi Kelompok Kerja Guru - Sardi Sardi (Publikasi Indonesia, 2022)
The Principal's Efforts in Improving the Ability of Teachers to Utilize the Environment as a Learning Resource By Using Teacher Working Group Discussions at SD Negeri 1 Jipangan, Banyudono District, Boyolali Regency, For the 2021/2022 Academic Year. This study aims to determine the ability of teachers to use the environment as a learning resource at SD Negeri 1 Jipangan, Banyudono District, Boyolali Regency. The results of this study show that through the Teacher Working Group can improve the ability of teachers to use the environment as a learning resource, this is because through the Working Group teachers feel that they have received input and know the shortcomings in implementing Utilizing the Environment as a Learning Resource. Based on the results of the study, it can be seen that through the Teacher Working Group, the ability of teachers to utilize the environment as a learning resource at SD Negeri 1 Jipangan, Banyudono District, Boyolali Regency, for the 2021/2022 Academic Year.